Multilayer diffusion-based molecular communication - Mustam, S. M. (Wiley Blackwell, 2017)
Diffusion-based molecular communication (DBMC) has emerged as a promising communication option, particularly for biomedical and healthcare applications. Although, numerous studies have been conducted to evaluate and analyse DBMC system, investigation on DBMC through multilayer channels has had less attention. In this paper, a closed-form expression is derived for the mean molecular concentration over an n-layer channel. An averaged diffusion coefficient for thin, dissimilar and multilayer propagation channels is determined through the addition of a diffusion resistance for each medium analogously to the sum of series resistors in circuit theory. The channel characteristics such as impulse response, time delay and attenuation are analytically obtained using amplitude detection technique. The effects of layer thickness and the distance between a transmitter nanomachine and a receiver nanomachine on the channel time delay and channel attenuation under the pulse modulation scheme are evaluated and discussed. The results show that increasing the diffusion coefficient leads to time delay decrements; however, the channel attenuation remains unchanged. Moreover, lengthening the transmission distance increases the time delay and decreases the channel attenuation. Copyright © 2015 John Wiley & Sons, Ltd.